EVALUATION OF BACKGROUND AND ENVIRONMENTAL FACTORS ON MENOPAUSAL RELATED SYMPTOMS - S Ayaty, (Babol University of Medical Sciences, 2008)
BACKGROUND AND OBJECTIVE: With respect to increasing life expectancy in women, and anticipation that about one third of their life will expand after menopause and many of complications and problems that go along with menopause, attention to improve the quality of life has an important role. The purpose of this study was to evaluate the relation between background environmental and socio demographic factors on menopausal symptoms.METHODS: This cross sectional study was done on 150 menopausal women who admitted to menopausal clinic of Ghaem hospital, Mashhad, Iran from Jan 2004 to Jul 2005. The data collected with a questionnaire including environmental and socio demographic and clinical symptoms of menopause such as physical activity, flushing, urogenital symptoms, smoking and history of hormone replacement therapy (HRT). FINDINGS: Educational state, smoking, physical exercise and history of HRT affected menopausal symptoms. Flushing and other menopausal symptoms were less common in educated women (p=0.014). Flushing and urogenital symptoms were decreased by more physical exercise (p=0.000 and p=0.03, respectively). Smoking would aggravate flushing (p=0.05). Previous HRT increases dyspareunia but it had no relationship with flushing and urogenital symptoms. BMI, marriage status, job, medical disease, history of OCP consumption, parity and menopausal age didn t affect menopausal symptoms. CONCLUSION: Life style modification and creating conditions for good health in women of pre and post menopausal age can decrease the menopausal related symptoms and enhance the quality of life after menopause.